Mycotoxins in artisanal beers: An overview of relevant aspects of the raw material, manufacturing steps and regulatory issues involved. (March 2021) - Schabo, Danieli C.; Freire, Luísa; Sant'Ana, Anderson S.; Schaffner, Donald W.; Magnani, Marciane
Graphical abstract: Highlights: Infected cereal grains are the main risk for beer contamination with mycotoxins. The transfer from wheat malt to beer varied among mycotoxins. There is a gap in the knowledge of aflatoxins fate during brewing. Emerging toxins may be present in artisanal beer. Abstract: The consumption of artisanal beer has increased worldwide. Artisanal beers can include malted or unmalted wheat, maize, rice and sorghum, in addition to the basic ingredients. These grains can be infected by toxigenic fungi in the field or during storage and mycotoxins can be produced if they find favorable conditions. Mycotoxins may not be eliminated throughout the beer brewing and be detected in the final product. In addition, modified mycotoxins may also be formed during beer brewing. This review compiles relevant information about mycotoxins produced by Aspergillus, Fusarium and Penicillium in raw material of artisanal beer, as well as updates information about the production and fate of mycotoxins during the beer brewing process. Findings highlight that malting conditions favor the production of mycotoxins by the fungi contaminating cereals. Therefore, good agricultural and postharvest mitigation strategies are the most effective options for preventing the growth of toxigenic fungi and the production of mycotoxins in cereals. However, the final concentration of mycotoxin in artisanal beer is difficult to predict as it depends on the initial concentration contained in the raw material and the processing conditions. The current lack of limits of mycotoxins in artisanal beer underestimates possible risks to human health. In addition, modified mycotoxins, not detected by conventional methods, may be formed in artisanal beers. Maximum tolerated limits for these contaminants must be urgently established based on scientific data about transfer of mycotoxins throughout the artisanal beer brewery process.